HUBUNGAN ANTARA FAKTOR INTERNAL DAN EKSTERNAL KELUARGA BURUH MIGRAN DENGAN KESEDIAAN UNTUK BERINVESTASI - Rina Damayanti Wulansari; Georgius Hartono; Rukmadi Warsito (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2014)
The purposes of this study are to determine: 1) the relationship between internal as well as external factors of Indonesian migrant workers’ family and their willingness to invest, 2) the types of investment made and the obstacles encountered, and 3) the amount of remittances received. The research was conducted in Pabelan and Tuntang Districts Semarang Regency by using explanatory research with quantitative and qualitative analyses approach. Data obtained from 80 respondents in earlier study entitled “Indonesian Labour Force: Roles and Impacht ono Rural Economy Central Jawa Province (2nd year)” and interviews with re-using 12 sampel of respondent. Spearman rank corelation and paired T-test at the confidence level of 95 percent were used to determine the magnitude of the relationship among assessed variables. Results of this study indicate that the internal and external factors of migrant labors’ family were strongly related to their willingness to invest. The types of investment were building a firm and buying land, cars, cattle or house. Saving money and purchasing motorcycle were considered thecombination of investment and consumptive goods, and household variable are buying consumer goods for labour’s families migrant. The barriers were faced by families of migrant labours, there was the urgency of daily life needs, house improvements, school fees, labour’s departure-relatedcosts and other debts . The amount of remittances associated with the willingness to invest is different among migrant labors working in varied countries. This is resulted from the different wagesstandard of each country of destination, labor’s departure fee discount, the working period, and the types of jobs abroad.